Simbolisme dalam puisi Apparition karya Stéphane Mallarmé - Ramadhani, Tri Nur Suci; Evi Rosyani Dewi; Subur Ismail (Franconesia, 2022)
This research aims to describe the elements of symbolism contained in the poem Apparition by Stéphane Mallarmé. In this research, there are four elements of symbolism referring to Wellek & Warren's the ory, namely image, metaphor, symbol, and myth. The research method used is content analysis using a qualitative structural approach to the work. Data analysis uses document analysis and refers to data analysis techniques with data sources, namely poetry with intrinsic elements in the analyzed poetry in the form of phonological elements and semantic elements. The results of this research indicate that there are 20 data in poetry that reflect the four elements of symbolism. Of the four elements of image symbolism, the dominant element is found in 14 lines, then the symbol element is found in 3 lines, the metaphor element is found in 2 lines, and the least found element is myth in 1 line.